The Future of Learning and the Future of Assessment. (September 2019) - Elmore, Richard F.
Purpose: The aim of this article is to point out that assessment should serve as useful information about the development of learners' capabilities, but not define, measure, evaluate, and confer "merit." Design/Approach/Methods: By arguing the current assessments are institutionalized which have deeply embedded social, cultural, and political purposes and ignoring learning at the individual or collective level, this article redefines learning, schooling, and assessment. Learning should be embodied, highly individualized, highly contextual, and lifelong, so schooling and assessment should support such learning form rather than perform attainment, custody, and control. Neurological basis of learning in human beings supports the new definition. Findings: Assessment should provide valuable information to guide, give feedback, and support the dynamic feature of learning. Future assessment is a tool to reflect how learners judge their learning, how they develop as a learning organism, and how they have the ability to develop agency and control over learning. Originality/Value: This article gives learning, schooling, and assessment new definitions combining the current situation and neurological evidence. It would be a thorough and novel guideline for the designing of future assessment.